IgE class immune complexes in Felty's syndrome: characterisation of antibody activities in isolated complexes. Issue 2 (April 1984) - Merétey, K; Falus, A; Böhm, U; Permin, H; Wiik, A
Abstract : By means of a double polyethylene glycol (PEG) precipitation and PRIST technique IgE was detected in 3% PEG precipitates and in the immune complex enriched fractions purified by solid-phase Clq adsorption from sera of 11 of 20 patients with Felty's syndrome. No correlation was found between the occurrence of complexed IgE and total protein content of the immune complex enriched material. IgE rheumatoid factor and anti-IgE antibody activity were detected in some of the immune complex fractions. Serum levels of complement C3, C4, and factor B were low in IgE immune complex positive cases. Only 4 of 20 patients with articular rheumatoid arthritis had IgE-containing immune complexes.